2021
DOI: 10.1038/s41598-021-82453-4
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the involvement of cilevirus p32 protein in the viral transport

Abstract: Citrus leprosis (CL) is a severe disease that affects citrus orchards mainly in Latin America. It is caused by Brevipalpus-transmitted viruses from genera Cilevirus and Dichorhavirus. Currently, no reports have explored the movement machinery for the cilevirus. Here, we have performed a detailed functional study of the p32 movement protein (MP) of two cileviruses. Citrus leprosis-associated viruses are not able to move systemically in neither their natural nor experimental host plants. However, here we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…The C-terminus of the MPs assigned to the 30K superfamily has been described to be a multifunctional region intrinsically implicated with several aspects of viral movement, such as interaction with the cognate capsid protein (CP), formation of tubular structures, and efficiency in viral cell-to-cell and systemic transport [10,13,46,52,53]. In our recent study, the sequential C-terminal deletion of CiLV-C2 MP showed that, although the absence of this fragment (deletion of 70 residues) still enables cell-to-cell movement, its removal impairs the correct tubule polymerization and MP-plasmodesma association, affecting the viral cellto-cell and long-distance transport; furthermore, this region is independently responsible to recruit the p29 (cilevirus capsid protein) to the cell periphery [34]. Consequently, any MP modification in this region could affect one or several viral movement processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The C-terminus of the MPs assigned to the 30K superfamily has been described to be a multifunctional region intrinsically implicated with several aspects of viral movement, such as interaction with the cognate capsid protein (CP), formation of tubular structures, and efficiency in viral cell-to-cell and systemic transport [10,13,46,52,53]. In our recent study, the sequential C-terminal deletion of CiLV-C2 MP showed that, although the absence of this fragment (deletion of 70 residues) still enables cell-to-cell movement, its removal impairs the correct tubule polymerization and MP-plasmodesma association, affecting the viral cellto-cell and long-distance transport; furthermore, this region is independently responsible to recruit the p29 (cilevirus capsid protein) to the cell periphery [34]. Consequently, any MP modification in this region could affect one or several viral movement processes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, any MP modification in this region could affect one or several viral movement processes. Given the positive effect in AMV transport by this amino acid change, it would be interesting to assess whether the presence of a putative alpha-helix structure at the carboxy-terminal of CiLV-C2 MP could favor the tubule formation and/or the MP association with plasmodesmata, since it has been shown that these processes were essential for an efficient AMV transport mediated by cilevirus MP [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P15, P61, and P24 are proteins without definitively associated functions, although the first two seem to be involved in the suppression of the RNA silencing mechanism ( Leastro et al, 2020 ) and the latter one is conserved among cileviruses, higreviruses, and an increasing number of arthropod-infecting viruses ( Kuchibhatla et al, 2014 ; Kondo et al, 2020 ; Ramos-González et al, 2020 ). The p32 encodes a movement protein (MP) of the 30K superfamily ( Mushegian and Elena, 2015 ; Leastro et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%